(untitled) (Third Sector Social Economic Review, 2025)
This research examines the role of social media in tourism marketing and its effects on tourists visiting Mardin. Using the relational screening model, one of the quantitative research methods, data was collected from 280 tourists visiting Mardin. The research analyzes the effect of social media use on tourist behaviors such as holiday destination selection, travel agency selection, and accommodation business selection. The findings show that gender and education status do not create a significant difference in social media behaviors, but there are differences according to demographic variables such as marital status, age, and monthly income. Single participants are more affected by social media in choosing a holiday destination compared to married participants. Individuals between the ages of 33-36 are more affected by social media in choosing a travel agency compared to those aged 42 and above. It was determined that individuals in the low-income group use social media more and are more affected by social media in choosing a holiday destination. The research revealed that social media use has a positive, moderate relationship with holiday destination, travel agency, and accommodation business selection. Most of the participants use social media for 2-3 hours a day and prefer Instagram the most. Mardin is preferred due to its historical and cultural richness, natural beauty, gastronomy and hospitality. It has been concluded that social media is an effective tool in promoting Mardin and can increase its tourism potential. Therefore, it is recommended to give more importance to the social media promotion of Mardin.Keywords: Mardin, Social Media, Tourism Marketing